UNIT 12.14 Measurement of Glucose Uptake in Cultured Cells. Issue 1 (8th December 2015) - Yamamoto, Norio; Ueda‐Wakagi, Manabu; Sato, Takuya; Kawasaki, Kengo; Sawada, Keisuke; Kawabata, Kyuichi; Akagawa, Mitsugu; Ashida, Hitoshi
Abstract : Facilitative glucose uptake transport systems are ubiquitous in animal cells and are responsible for transporting glucose across cell surface membranes. Evaluation of glucose uptake is crucial in the study of numerous diseases and metabolic disorders such as myocardial ischemia, diabetes mellitus, and cancer. Detailed in this unit are laboratory methods for assessing glucose uptake into mammalian cells. The unit is divided into five sections: (1) a brief overview of glucose uptake assays in cultured cells; (2) a method for measuring glucose uptake using radiolabeled 3‐ O ‐methylglucose; (3) a method for measuring glucose uptake using radiolabeled 2‐deoxyglucose (2DG); (4) a microplate method for measuring 2DG‐uptake using an enzymatic, fluorometric assay; and (5) a microplate‐based method using a fluorescent analog of 2DG. © 2015 by John Wiley & Sons, Inc.